2009
DOI: 10.1021/ja808807s
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of Phobanes. Diastereoselective Synthesis of the Three Isomers ofn-Butylphobane and a Comparison of their Donor Properties

Abstract: Three methods for the large scale (50-100 g) separation of the secondary phobanes 9-phosphabicyclo[3.3.1]nonane (s-PhobPH) and 9-phosphabicyclo[4.2.1]nonane (a-PhobPH) are described in detail. Selective protonation of s-PhobPH with aqueous HCl in the presence of a-PhobPH is an efficient way to obtain large quantities of a-PhobPH. Selective oxidation of a-PhobPH in an acidified mixture of a-PhobPH and s-PhobPH is an efficient way to obtain large quantities of s-PhobPH. The crystalline, air-stable phosphonium sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 58 publications
4
47
0
Order By: Relevance
“…separated from the expected product 4 by column chromatography. Phospholane boranes 4 and 5 were identified by 31 P, 13 C, and 1 H NMR, as well as mass spectral data. The 31 P NMR spectrum of 4 comprised two broad signals, whereas that of 5 showed a broad signal for the ring P and a doublet of 29.9 Hz for the exocyclic P-function.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…separated from the expected product 4 by column chromatography. Phospholane boranes 4 and 5 were identified by 31 P, 13 C, and 1 H NMR, as well as mass spectral data. The 31 P NMR spectrum of 4 comprised two broad signals, whereas that of 5 showed a broad signal for the ring P and a doublet of 29.9 Hz for the exocyclic P-function.…”
Section: Methodsmentioning
confidence: 99%
“…Heterocyclic P-ligands occurring in Pt(II) complexes, comprise, among others [6][7][8], arylphospholes [9,10], phospholenes [11], phospholanes [11,12], phosphinine (phosphorine) derivatives [11,12], phosphepanes [12], as well as 9-phosphabicyclononanes (Phobanes) [13] and 6-phospha-2,4,8-trioxaadamantanes [14].…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, tricyclohexylphosphane is slightly more bulky than isobutylphobane, as expressed by the Tolman cone angle (q = 1708 for PCy 3 [58] and 1638 for i-BuPhob [59] ). For nonobvious reasons, it is also a better electron donor, as measured from the values of n(CO) in trans-[RhCl(CO)A C H T U N G T R E N N U N G (PR 3 ) 2 ] complexes (1943 cm À1 for PCy 3 [60] vs. 1950 cm À1 for i-BuPhob [61] ).…”
Section: Mechanistic Indicationsmentioning
confidence: 99%
“…Prigle et al reported the synthesis of the platinum complexes of several 5-, 6-and 7-membered P-heterocycles [33,34]. Gouygou et al synthesized a few bisphosphole platinum-complexes [35].…”
Section: Introductionmentioning
confidence: 99%